Growing Currency Reserves in Asia and their Consequences - Żukrowska, Katarzyna (Rosnące rezerwy walutowe w Azji i ich konsekwencje, 2010)
Sequencing in international economic relations goes through clearly cut stages of development. Asia's economic weight in the world has risen but this rise is smaller than commonly assumed.1 Asian economies competed in the past for inward flows of capital, which have stimulated growth, development and brought into the economies of the region advanced technologies, know-how and international corporations as well as they have caused restructuring of the economies. The article concentrates on consequences in development of the Asian economies and their engagement in the main stream of the world economy, which have resulted in the currently noted increase of currency reserves enforcing special decisions concerning economic policy on flows of capital.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 204-215
Keywords: Asia; currency reserves; flow of capital